2002
DOI: 10.1038/sj.bjc.6600282
|View full text |Cite
|
Sign up to set email alerts
|

Increase in immune cell infiltration with progression of oral epithelium from hyperkeratosis to dysplasia and carcinoma

Abstract: In the present study, epithelium derived lesions of various pathological manifestations were examined histologically and immunohistochemically for mononuclear cell infiltration. The infiltrate under the transformed epithelium of oral lesions, was examined for differences in the composition of immune mononuclear cells as the epithelium moves from hyperkeratosis through various degrees of dysplasia to squamous cell carcinoma. The study was performed on 53 human tongue tissues diagnosed as hyperkeratosis (11 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 16 publications
10
64
0
1
Order By: Relevance
“…Gannot et al also documented increasing levels of subepithelial inflammatory infiltrate (sometimes referred to as lichenoid inflammation) in oral tissue during progression from normal to dysplasia to Research. (35). A second investigation found that stromal T cells increased by roughly a factor of 2 in mild dysplasias, and by f5-fold in moderate and severe dysplasia compared with normal oral tissue (36).…”
Section: Discussionmentioning
confidence: 99%
“…Gannot et al also documented increasing levels of subepithelial inflammatory infiltrate (sometimes referred to as lichenoid inflammation) in oral tissue during progression from normal to dysplasia to Research. (35). A second investigation found that stromal T cells increased by roughly a factor of 2 in mild dysplasias, and by f5-fold in moderate and severe dysplasia compared with normal oral tissue (36).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Pollard reported that the infiltration of macrophages stimulated breast cancer progression and metastasis (Pollard, 2004), and knocking out colony-stimulating factor-1 (CSF-1, a cytokine that regulates macrophage differentiation and function) in a mouse strain inhibited breast cancer growth and metastasis. A study on oral epithelial squamous cell carcinoma also revealed that the level of immune cell infiltration was positively correlated with the level of morphological and pathological transformation from normal to malignant phenotypes (Gannot et al, 2002).…”
Section: Tlrs Cancer Cells and The Tumor Immune Infiltratementioning
confidence: 99%
“…Many human and murine tumors are heavily infiltrated by B cells (1)(2)(3)(4), but their role in regulating anti-tumor immunity is not well understood. A variety of murine tumors are either completely rejected or demonstrated reduced growth in the absence of B cells, including the EL-4 thymoma, MC38 colon carcinoma and the EMT-6 breast carcinoma, D5 mouse melanoma (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%